2019
DOI: 10.1093/femspd/ftz051
|View full text |Cite
|
Sign up to set email alerts
|

Non-pigmented rapidly growing mycobacteria smooth and rough colony phenotypes pathogenicity evaluated usingin vitroand experimental models

Abstract: Non-pigmented rapidly growing mycobacteria (NPRGM) are widely distributed in water, soil and animals. It has been observed an increasing importance of NPRGM related-infections, particularly due to the high antimicrobial resistance. NPRGM have rough and smooth colony phenotypes, and several studies have showed that rough colony variants are more virulent than smooth ones. However, other studies have failed to validate this observation. In this study, we have performed two models, invitro and in vivo, in order t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…More recently, Roux et al [ 18 ] used a macrophage cell culture model and showed that R M. abscessus cells were able to multiply inside the cells, while S cells were not. This model has been used more recently with other species, showing that the R strains of both M. abscessus and other RGM can survive inside the macrophages more easily than the S strains [ 25 ].…”
Section: Models Of Intracellular Survivalmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, Roux et al [ 18 ] used a macrophage cell culture model and showed that R M. abscessus cells were able to multiply inside the cells, while S cells were not. This model has been used more recently with other species, showing that the R strains of both M. abscessus and other RGM can survive inside the macrophages more easily than the S strains [ 25 ].…”
Section: Models Of Intracellular Survivalmentioning
confidence: 99%
“…Moreover, studies evaluating murine models described a limited ability to induce chronic infection that simulates pulmonary infection in humans [ 29 ]. Therefore, alternative non-mammalian models, such as Galleria mellonella moth larvae, Drosophila melanogaster, and zebrafish embryos have been developed to study both host and mycobacterial determinants of pathogenesis during chronic infection with M. abscessus [ 25 , 29 , 30 ].…”
Section: Models Of Intracellular Survivalmentioning
confidence: 99%
See 1 more Smart Citation
“…Rough colonies induce a proinflammatory response as part of a severe infection resulting in massive tissue destruction [ 17 ]. Different in vivo models have shown that rough morphotypes are more virulent than smooth variants [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…A murine neutropenic model, in which neutropenia is induced by intraperitoneal doses of cyclophosphamide, has also been exploited to demonstrate the in vivo efficacy of drugs against M. fortuitum and M. abscessus (Das et al, 2019). In addition, a recent study highlighted the suitability of the Galleria mellonella moth larvae as a cheap, efficient and rapid in vivo model for the screening of antibiotic combinations and novel treatments against NTM, including M. fortuitum (Entwistle and Coote, 2018;García-Coca et al, 2019).…”
Section: Introductionmentioning
confidence: 99%